Cellular immunity in systemic lupus erythematosus as evidenced in vitro by leucocyte migration inhibition tests. Issue 5 (October 1977) - Okubo, M; Nagura, Y; Pompa, D; Treser, G; Lange, K
Abstract : A leucocyte migration inhibition test was performed on 26 patients with systemic lupus erythematosus (SLE) and on 35 control subjects using three different antigens, fetal calf thymus DNA, baker's yeast RNA, and calf thymus extractable nuclear antigen (ENA). Leucocyte migration was inhibited by DNA in 17 out of 26 SLE patients (65-3%), and in only 2 of the 35 controls (5-7%). When RNA or ENA was added none of the patients or controls showed inhibition. In SLE patients migration inhibition by DNA was significantly correlated with the presence of proteinuria and/or granular casts in urinary sediment. When the migration inhibition test was positive, immunofluorescence verified active histology of the glomeruli obtained by a percutaneous renal biopsy.